Antioxidant properties, prebiotic effect and intestinal protection of wheat and barley enriched diets in male Wistar rats - KECHIDA Khadidja; MOKRANI Nour Elhouda; NAMOUSSA Karima (Université of Eloued, 2024)
The purpose of this study is to evaluate the influence of wheat and barley-derived prebiotics on gut microbiota and health parameters in Wistar rats. Wheat (Triticum aestivum) and barley (Hordeum vulgare) were selected as prebiotics and harvested in the El Oued region. The study assesses the in vivo biological effects of a diet rich in wheat and barley. Male Wistar albino rats were fed a diet comprising 30% prebiotics (wheat and barley) and 70% mabroma for two weeks. We assessed malondialdehyde (MDA), glutathione (GSH), and catalase (CAT) activity in the liver, kidneys, brain, and blood, as well as conducted histological examinations of the colon and bacterial analysis. In rats fed a wheat and barley diet, MDA levels, as well as CAT and GSH activity, were notably higher than in controls. For instance, the brain exhibited greater MDA levels for wheat, barley, and wheat-barley combination groups (4.32±0.44 µmol/l), (4.37±0.76 µmol/l), and (4.29±0.28 µmol/l), respectively, compared to the normal group (2.47±0.89 µmol/l). Additionally, the wheat group rats had a higher MDA level in their blood (3.73±1.37 µmol/l) compared to the normal group. Regarding GSH, all values were high, even for the control group. For example, the wheat group (2.37±0.38 µmol/mg) and barley group (2.30±0.27 µmol/mg) had higher kidney values than the normal group (2.27±0.21 µmol/mg). Histological study revealed that treated rats had thicker colons with a significant increase in total wall thickness in the colon of rats fed on wheat+barley (258.80μm) and barley (192.77μm) compared to the normal group (133.32μm), with differences of 125.48μm and 59.45μm, respectively. Additionally, beneficial microorganisms such as Leuconostoc mesenteroides were discovered. Thus, our data show that wheat and barley prebiotics improve colon thickness, exhibit antioxidant effects, and positively influence gut microbiota and health parameters in vivo.
Keywords: prebiotics; wheat; barley; biological activities; gut microbiota